1975
DOI: 10.3109/inf.1975.7.issue-1.06
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Significance of Hemolytic Streptococci Groups B–U in Human Infectious Disease

Abstract: 245 strains of hemolytic streptococci, isolated from 225 patients with infectious diseasses, were grouped serologically according to Lancefield. About 40% belonged to group B and half of them were found in the genito-urinary tract. Another 40% belonged to the groups C and G, half of them being found in the respiratory tract and often as the only potentially pathogenic organism. About 10% of the isolates belonged to other of the groups E to T, including M streptococci, and were found under similar circumstances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1980
1980
1990
1990

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…These authors also reported a 56-year-old woman who developed septicaemia after an attack of thrombophlebitis in the leg (Bevanger & Stamnes, 1979); the patient was often in contact with dogs. /?GLS were first found in the human throat by White, Rudd & Ward (1939) in a study of patients with scarlet fever in Australia (strains 'Hooper' and 'Krone': see Wilson & Miles, 1946), and have since been found at this site in patients both with (Nordlander, Thal & Tunevall, 1975) and without (Olsen, 1957) signs of respiratory infection. They have been found on the normal skin of pig farmers (Olsen, 1957) and, together with Staph.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors also reported a 56-year-old woman who developed septicaemia after an attack of thrombophlebitis in the leg (Bevanger & Stamnes, 1979); the patient was often in contact with dogs. /?GLS were first found in the human throat by White, Rudd & Ward (1939) in a study of patients with scarlet fever in Australia (strains 'Hooper' and 'Krone': see Wilson & Miles, 1946), and have since been found at this site in patients both with (Nordlander, Thal & Tunevall, 1975) and without (Olsen, 1957) signs of respiratory infection. They have been found on the normal skin of pig farmers (Olsen, 1957) and, together with Staph.…”
Section: Discussionmentioning
confidence: 99%
“…Beta-haemolytic, Lancefield group L streptococci (/JGLS) have been found in healthy carriage or infection in many animals, including poultry (Barnham, Kerby & Skillin, 1982), pigs (Olsen, 1957;Olsen, 1964;Jones, 1976aJones, , b, 1981, cattle (Olsen, 1957; Klastrup, 1963;Jensen et al 1958;Wilson & Salt, 1978), sheep (Thal & Moberg, 1953), dogs (Stableforth & Galloway, 1959;Laughton, 1948) and other small fur-bearing animals (Thal & Moberg, 1953). They have been occasionally found in the human throat (Olsen, 1957;White, Rudd & Ward, 1939;Nordlander, Thal & Tunevall, 1975), but infection in man appears to be rare: there are reports of septicaemia and endocarditis (Bevanger & Stamnes, 1979;Ellner, 1970), skin infection (David & Cambridge, 1986) and abscess in the hand of a butcher (Duma et al 1969).…”
Section: Introductionmentioning
confidence: 99%
“…The organism was first described in 1935 by Lancefield and Hare (1). Group G streptococci may be found as a member of the normal flora of the pharynx, intestine, vagina and skin (1,2), and as a pathogen in infections such as endocarditis, septic arthritis, pharyngitis, puerperal sepsis, peritonitis, pleuropulmonary infections, meningitis, cellulitis, otitis media and neonatal sepsis (3,4). Septicemia, although infrequently reported in the literature, has been the most common clinical manifestation of group G streptococcal infections.…”
mentioning
confidence: 99%